Immunological characterization of Vibrio cholerae O:1 lipopolysaccharide, O-side chain, and core with monoclonal antibodies. - Gustafsson, B (1985)
Lipopolysaccharide (LPS) was extracted from Vibrio cholerae O:1 strains of the serotypes Ogawa, Inaba, and Hikojima and delipidated by mild-acid hydrolysis. Two polysaccharide fragments with the molecular weights of approximately 9,000 and 900, respectively, were isolated by gel permeation chromatography. The LPS preparations and the polysaccharide fragments were studied in enzyme-linked immunosorbent assay inhibition, rocket immunoelectrophoresis, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by electroblotting with monoclonal antibodies directed against the group-specific antigen A, the type-specific antigens B (Ogawa) and C (Inaba), and the core region. Antigen A was demonstrated in all LPS preparations and all 9,000-molecular-weight fragments tested. The type-specific antigens B and C were demonstrated in LPSs and 9,000-molecular-weight fragments from Ogawa and Inaba, respectively. Furthermore, antigens B and C were both demonstrated in LPSs and 9,000-molecular-weight fragments from two of four Hikojima strains tested. Core antigen was demonstrated in the LPS and in the 9,000- and 900-molecular-weight fragments. The results indicate that the 9,000-molecular-weight fragment represents the complete polysaccharide chain, including group- and type-specific antigens as well as core antigens, whereas the 900-molecular-weight fragment constitutes the main part of the core region.